Cover Image, Volume 26, Issue 1. (14th December 2017) - Becerril‐Romero, Ignacio; Acebo, Laura; Oliva, Florian; Izquierdo‐Roca, Víctor; López‐Marino, Simón; Espíndola‐Rodríguez, Moisés; Neuschitzer, Markus; Sánchez, Yudania; Placidi, Marcel; Pérez‐Rodríguez, Alejandro; Saucedo, Edgardo; Pistor, Paul
Abstract : The cover image, by Ignacio Becerril‐Romero et al., is based on the Research Article CZTSe solar cells developed on polymer substrates: Effects of low‐temperature processing, DOI:10.1002/pip.2945 .